2020
DOI: 10.1111/1750-3841.15560
|View full text |Cite
|
Sign up to set email alerts
|

Physical characterization of high methoxyl pectin and sunflower oil wax emulsions: A low‐field 1H NMR relaxometry study

Abstract: Pectin–wax‐based emulsion systems could be used to form edible films and coatings with desired water permeability characteristics. Pectin is often used in food industry due to its gelling and viscosity increasing properties. Physical properties of pectin are highly dependent on its esterification degree. Waxes are commonly used as edible coatings to enhance the water barrier properties of food products. This study focuses on preparing emulsions with sunflower oil wax (SFW) and high methoxyl pectin (HMP) at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…T2 relaxation time [30]. Similar findings were observed by Han and Bertram [31] when pectin was added to meat-based products.…”
Section: Low Field Nuclear Magnetic Analysis (Lf-nmr) Analysissupporting
confidence: 85%
See 1 more Smart Citation
“…T2 relaxation time [30]. Similar findings were observed by Han and Bertram [31] when pectin was added to meat-based products.…”
Section: Low Field Nuclear Magnetic Analysis (Lf-nmr) Analysissupporting
confidence: 85%
“…The high proportion of tightly bound water in CU-601 and CU-201 samples may be due to the hydrophilic nature of these types of pectin. As discussed earlier, if molecules are closely arranged or have a shorter distance, a high energy efficiency is achieved, which will produce shorter T 2 relaxation time [30]. Similar findings were observed by Han and Bertram [31] when pectin was added to meat-based products.…”
Section: Low Field Nuclear Magnetic Analysis (Lf-nmr) Analysissupporting
confidence: 81%
“…The T 2 and its corresponding peak area were used to reflect the mobility of water molecules containing hydrogen protons [ 11 ]. They are correlated with the extent of protein proton exchange, water proton exchange, and the interaction between water components and other polymers in gelation process [ 16 , 41 ]. The relative signal intensities (T 21 , T 22 , and T 23 ) represent bound water, semi-bound water, and free water, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These issues can be potentially addressed by low-field NMR (LF-NMR) spectroscopy, which has been widely used as a powerful analytical tool in food analysis for quality monitoring and process supervision [ 17 , 18 , 19 , 20 ]. For example, Ancora et al [ 21 ] demonstrated that LF-NMR relaxation measurements could be applied to determine the occurrence of adulteration in EVOO samples when mixed with four different edible vegetable oils.…”
Section: Introductionmentioning
confidence: 99%